Orchids of UNIMAS : Diversity in a Developed Campus Landscape - Almunah, Abd Mutalib; Akmal, Raffi; Meekiong, Kalu; Farah Alia, Nordin (UNIMAS Publisher, 2024)
For the past three decades, various biotic components in Universiti Malaysia Sarawak (UNIMAS) natural habitats have been studied but less attention given to the largest family of flowering plants, the Orchidaceae. A preliminary survey in the campus areas has resulted in the discovery of more than ten species of orchids. Therefore, in this study more field samplings were conducted throughout the UNIMAS campus focusing on the developed areas to unveil the potential of UNIMAS-developed areas as a growth ground for orchids. To date, 37 orchid species have been recorded from these areas; mainly found on the planted trees at the roadside and landscaped areas surrounding the academic buildings, while the terrestrial species were found to inhabit different types of disturbed habitat. Among them, Dendrobium pensile was identified as a new record to Sarawak while Dendrobium pseudostriatellum and Pinalia biglandulosa were endemic to Borneo. This study provides an insight into the orchid resiliency towards habitat alteration, landscape phorophytes species that can host orchids, and management of species in a developed landscape